Breeding Place Preference of Aedes sp. at the Tsunami Area Banda Aceh City - Agustina, Elita; Emil, Muhammad Farhan Putra (Universitas Ahmad Dahlan, 2024)
The rebuilding of the post-tsunami community residential in Banda Aceh has had an impact on the emergence of Aedes habitat. The Aedes choose a container to breed based on biotic and abiotic factors that support their survival. This study aimed to the identification of Aedes species, location and type positive containers Aedes larvae at the area tsunami Banda Aceh. Methods an observational study of a cross-sectional approach involved 100 houses. Data larvae were collected using the single larvae method. Observations of containers were carried out in natural and artificial containers, indoors and outdoors. Positive containers Aedes larvae were recorded for the type of container and location found. The result of the study found two species of Aedes, there were Aedes aegypti and Aedes albopictus. Larvae of Ae. aegypti was generally found in containers indoors (71%) and containers outdoors (29%). Larvae of Ae. albopictus were found in containers indoors (10%) and containers outdoors (90%). The types of positive breeding containers of Ae. aegypti found were bathtubs (71%), discarded tires (9%), plastic drums (5%), water tanks (5%), watering pots (5%) and flower pots (5%). The containers were observed found larvae of Ae. albopictus were the bucket (30%), plastic drum (20%), bathtub (10%), discarded tires (10%), pet drinking place (10%), mineral water jar (10%) and coconut shells (10%). Monitoring of containers indoors and outdoors that can hold water is important supports the eradication program breeding places of Ae. aegypti and Ae. albopictus.